Strategi Guru Dalam Meningkatkan Minat Berbicara Bahasa Arab Siswa SMK Full Day Sunan Ampel Banyuwangi - Ilham Nur Kholiq; Azam Fadli (Institut Agama Islam Darusssalam Blokagung, 2022)
This research purpose to determine the teacher's strategy in increasing interest in speaking Arabic for the students of SMK Full Day Sunan Ampel Banyuwangi. This type of research is descriptive qualitative research. The process of data collection was carried out using three ways, namely: observation, interviews and documentation. The data analysis technique uses an interactive model. And test the validity of the data using triangulation. The results showed that the Arabic teacher's strategy in increasing speaking interest at the Sunan Ampel Banyuwangi Full Day Vocational School was the Team Building Strategy and the Quantum Strategy. The Team Building Strategy is a great opening strategy for students who already know each other. This strategy can result in rapid team building. And Quantum Strategy is a strategy that provides specific instructions for creating an effective learning environment, designing curriculum, delivering content and facilitating the learning process.